A comprehensive pan-cancer analysis of LRFN4: its potential as a prognostic biomarker and therapeutic target for immunotherapy - Xu, Yinmei; Wu, Xin; Zhi, Peng; Guo, Genyu; Fu, Yankan; You, Lukuan; Huai, Siyuan; Li, Jianxiong (Frontiers in Immunology, 2025)
BackgroundLRFN4, characterized by leucine-rich repeats and fibronectin type III domains, has been implicated in various human diseases. However, its role in immune regulation and cancer prognosis remains unclear.MethodsWe performed a comprehensive analysis using datasets from The Cancer Genome Atlas (TCGA), Cancer Cell Line Encyclopedia (CCLE), Genotype-Tissue Expression Project (GTE x), UALCAN, Star Base, and Comparative Toxicogenomics Database (CTD), and observed significant dysregulation of LRFN4 in multiple cancers compared to normal tissues.ResultsLRFN4 expression was strongly correlated with clinical prognosis, immune subtypes, molecular subtypes, immune checkpoint (ICP) genes, tumor mutational burden (TMB), microsatellite instability (MSI), and immune infiltration, which were measured by ESTIMATE scores. Moreover, LRFN4 expression was associated with the presence of tumor-infiltrating immune cells, particularly in gastrointestinal tumors, reflecting immune cell genetic signatures. Validation through fluorescence multiplex immunohistochemistry confirmed that the association of LRFN4 protein expression with the clinicopathological features and the immune microenvironment of gastric cancer. Flow cytometry analysis indicated that LRFN4 inhibited apoptosis in gastric cancer cell lines while enhancing cell cycle arrest in the S phase. Western Blot analysis demonstrated a positive correlation between the high expression of LRFN4 and the expression levels of cyclin D1 as well as CDK4. In contrast, a negative correlation was observed between the high expression of LRFN4 and the expression level with cleaved-caspase-3 levels.ConclusionThese findings suggest that LRFN4 may serve as a novel biomarker for cancer prognosis and a potential target for immunotherapy.